Experimental and thermodynamic study of Li‐O and Li2O‐P2O5 systems. (21st February 2019) - Jin, Liling; Wang, Jian; Rousselot, Steeve; Dollé, Mickaël; Chartrand, Patrice
Abstract: LiFePO4 (LFP) as a promising cathode material has been extensively studied. However, the high cost of current batch production technology limits its application, especially in automotive industries. To develop the new melting synthesis of LFP, the process conditions have to be strictly controlled, such as temperature, composition, and the partial pressure of oxygen. Reliable and accurate thermodynamic information about Li‐Fe‐P‐O systems could serve as a useful guide for designing operating conditions. As part of ongoing efforts, the Li‐O and Li2 O‐P2 O5 binary systems have been first studied following the CALPHAD method using FactSage thermodynamic software. The data on thermodynamic properties ( C p, enthalpy of formation, and vapor pressure) and phase diagrams (liquidus/solidus temperature, phase transition, and solid solubility) available in the literature were carefully reviewed and evaluated for the above‐mentioned systems. The modified quasichemical model (MQM) with quadruplet approximation was used for the liquid phase in the present studies. This model simultaneously takes into account the short‐range ordering of first‐nearest‐neighbours (FNN) and second‐nearest‐neighbours (SNN), which improves the thermodynamic description of the Gibbs energy of the liquid. The thermodynamic model parameters of the Gibbs energy have been obtained for all of the phases considered in the Li‐O and Li2 O‐P2 O5 binary systems. DSC‐TGA experiments on the selected four compositions were carried out to validate the liquidus and phase transition temperature reported in the literature. Overall, the self‐consistent thermodynamic description using the model parameters obtained in this work can successfully reproduce the evaluated experimental data.